2003
DOI: 10.1021/es026131c
|View full text |Cite
|
Sign up to set email alerts
|

Sediment Conditioning with Organic and/or Inorganic Carbon Sources as a First Step in Alkalinity Generation of Acid Mine Pit Lake Water (pH 2−3)

Abstract: Laboratory scale microcosm studies were conducted to determine the efficacy of controlled in situ saprobization of lake sediments as one opportunity for deacidification of artificial shallow lakes resulting from open cast lignite mining located in southeast Germany. Under lasting anoxic conditions iron and sulfate were removed from the lake water as a result of microbial iron-and sulfate reduction together with a subsequent precipitation of insoluble sulfide minerals to the lake sediment. The 2 L closed system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 45 publications
(56 reference statements)
2
29
0
1
Order By: Relevance
“…Given the high pH achieved, most of the remaining metals are likely to have been precipitated as insoluble oxyhydroxides or as amorphous sulphur minerals (probably metal monosulphides (Suits and Wilkin 1998) in the upper and middle sediment strata. The middle strata contained moderate amounts of pyrite, which was probably derived from secondary mineralisation of the amorphous minerals (Frömmichen et al 2003;Praharaj and Fortin 2004). The presence of gypsum as the main sulphur mineral in the bottom strata may suggest that this stratum was laid down prior to the mine water addition, when the lower Fe concentrations in the water would have favoured gypsum rather than pyrite formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the high pH achieved, most of the remaining metals are likely to have been precipitated as insoluble oxyhydroxides or as amorphous sulphur minerals (probably metal monosulphides (Suits and Wilkin 1998) in the upper and middle sediment strata. The middle strata contained moderate amounts of pyrite, which was probably derived from secondary mineralisation of the amorphous minerals (Frömmichen et al 2003;Praharaj and Fortin 2004). The presence of gypsum as the main sulphur mineral in the bottom strata may suggest that this stratum was laid down prior to the mine water addition, when the lower Fe concentrations in the water would have favoured gypsum rather than pyrite formation.…”
Section: Discussionmentioning
confidence: 99%
“…Most published studies into the feasibility of SRB treatment systems have focused on highly labile, yet potentially expensive carbon substrates such as ethanol (Martin et al 2003;Kolmert et al 2001), sugar (Frömmichen et al 2003(Frömmichen et al , 2004Pöhler et al 2002), and cow manure (Drury 1999(Drury , 2000. However, many authors have now reported that the viability of this approach requires an organic matter source that is effective, economical, and locally available (Castro and Moore 1997;McCullough et al 2006b).…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, the use of largely fresh green waste as opposed to refractory organic substrates such as straw (Frömmichen et al, 2003;Frömmichen et al, 2004), rye grass (Harris and Ragusa, 2000;Harris and Ragusa, 2001), etc., distinguishes this research from many others in the published literature. The greater labile fraction of organic material available in this fresher material may have contributed directly to electron donors for SO 4 -2 reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Hard et al (2003) echoed this view noting that, "For a microbial process to be economically feasible, the carbon (C) and energy source should be cheap, widely available and highly effective." However, most experiments into the utility of SO 4 -2 reduction processes for ameliorating AMD have instead focused upon highly labile but expensive C substrates such as ethanol (Kolmert and Johnson, 2001;Martin et al, 2003;McNee et al, 2003), sugar (Frömmichen et al, 2003;Frömmichen et al, 2004;Geller et al, 2003;Pöhler et al, 2002;Wendt-Potthoff et al, 2002), cow manure (Drury, 1999;Drury, 2000), etc. For many remote mining locations, these materials are unviable for practical and economic reasons.…”
Section: Equationmentioning
confidence: 99%
“…Labile organic substrates with low molecular weights, such as acetate, lactate, ethanol, glucose, and treacle, have been evaluated for their efficiency in stimulating and promoting bacterial sulfate reduction for treatment of AMD (Frömmichen et al 2003(Frömmichen et al , 2004Meier et al 2004). However, it is impractical to use most of these labile compounds for field applications due to the high costs of purchasing, storing, and transporting the quantities required (Neculita et al 2007).…”
Section: Introductionmentioning
confidence: 99%